ANALISIS KETERAMPILAN MENULIS KHAT NASKHI SISWA KELAS X MADRASAH ALIYAH PADA MATA PELAJARAN AL-QURAN HADIST DI PP. KH. AHMAD DAHLAN KUANTAN SINGINGI - Sarifuddin Siregar; Bustanur Bustanur; Helbi Akbar (Universitas Islam Kuantan Singingi, 2020)
In the process of learning activity at school, it could not separated from writing activity by using Arabic writing, especially on Al- Qur’an and Hadits subject. Because writing were used for writing, recording, reporting, informating and influecing to the readers. Therefore, it needed an accuracy and precision in writing Al Qur’an and Hadits words. Because, small mistake in writing could change the true meaning. For good seing, it needed the rules of Khat Naskhi in writing. In observating, the writer found some symptoms that related to the students Khat Naskhi writing skill at the tenth grade were: 1) There were still mistakes in writing Arabic, 2) the teacher difficulty reading students’ writing because, they doing looks carelessly in writing, 3) student were slow in writing Arabic, 4) student writing was not neat, where many scribbless in the book. In the field research, the writer interested to research this case aimed at knowing how students’ Khat Naskhi writing skill at the tenth grade. The writer used test and documentation for collecting the data as the tool to measure the variables researching. In analyzing the data, the writer used classification technique that obtained from the student precentage score. After doing the research, so, it could be concluded that students’ Khat Naskhi writing skill on Al Qur’an hadits subject with the help classification, the precentage was on “Less skill” category . It meant that student Khat Naskhi writing skills at the Tenth Grade of Islamic Senior High School on Al Qur’an Hadits subject at Islamic Boarding School K.H. Ahmad Dahlan, Kuantan Singingi was on “Less skill” category.